2016
DOI: 10.3390/nu8080447
|View full text |Cite
|
Sign up to set email alerts
|

Selection of the Optimal Herbal Compositions of Red Clover and Pomegranate According to Their Protective Effect against Climacteric Symptoms in Ovariectomized Mice

Abstract: This study aimed to ascertain the optimal range of red clover dry extracts (RC) and dried pomegranate concentrate powder (PCP) to induce anti-climacteric effects. Thus, the dose ranges showing protective effect of mixed formulae consisting of RC and PCP were examined in ovariectomized mice. At 28 days after bilateral ovariectomy (OVX), mixed herbal compositions (RC:PCP = 1:1, 1:2, 1:4, 1:8, 2:1, 4:1, and 8:1) were administered orally, at 120 mg/kg once daily for 84 days. We evaluated that RC and PCP mixture at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 81 publications
0
20
0
Order By: Relevance
“…BMD, regarded as a valuable index of bone quality changes in clinical settings, is significantly decreased in osteoporotic animals, regardless of the cause (Diez, ; Joo et al, ; Jung et al, ; Kang et al, ; Syed & Khan, ). BMD has provided good predictive information about the efficacy of antiosteoporotic agents (Syed & Khan, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…BMD, regarded as a valuable index of bone quality changes in clinical settings, is significantly decreased in osteoporotic animals, regardless of the cause (Diez, ; Joo et al, ; Jung et al, ; Kang et al, ; Syed & Khan, ). BMD has provided good predictive information about the efficacy of antiosteoporotic agents (Syed & Khan, ).…”
Section: Resultsmentioning
confidence: 99%
“…Bone strength also markedly decreased in osteoporosis, regardless of the cause (Diez, ; Joo et al, ; Jung et al, ; Kang et al, ; Syed & Khan, ). The strength (FL) of the right dry femur and tibia mid‐shaft regions in OVX control rats were significantly ( p < .01) decreased compared with those of the sham control rats.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is a need to develop an efficient resorptive inhibitor with higher safety. On-going trials to develop anabolic agents are typically designed through understanding bone formation and the differences in osteoblast [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the various pharmacological effects of natural products are synergistically increased by appropriate mixed formulations [ 9 , 44 46 ]. Specifically, the bone-preserving characteristics of EAP have been potentiated by combining it with other active agents [ 47 49 ].…”
Section: Introductionmentioning
confidence: 99%